PERAN STAKEHOLDERS DALAM PENGEMBANGAN DESA WISATA MERANTI UTARA KABUPATEN TOBA PROVINSI SUMATERA UTARA - Kamelia Sentosa Panjaitan; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Meranti Utara Village is a village located in Pintu Pohan Meranti District, Toba Regency, North Sumatra Province. The geographical location of the sub-district which is quite outside among the sub-districts in Toba Province makes the village get little attention from the government. With a unique geographical location where Meranti Utara village is the border between two regencies, namely Toba Regency and Asahan Regency, it makes tourists busy visiting Meranti Utara village. Meranti Utara Village can be reached for 1 hour from the Lake Toba tour, which has been designated as a Priority Tour. The tours that are in great demand by tourists in this village are Ponot Waterfalls, Sialogo Waterfalls, Siarimo Waterfall tours, and the Asahan River which are used by the community as rafting potential. The development of tourism objects in Meranti Utara village is motivated through the role of inner stakeholders, specifically primary stakeholders as key stakeholders who've roles as implementers, coordinators, implementers, partners and facilitators. In the meantime, outside stakeholders encompass secondary or helping stakeholders who act as facilitators. Keyword : Tourist Village, The Role, Stakeholders, Meranti Utara Village